ANALISIS PENERAPAN MANAJEMEN RISIKO K3 PADA KARYAWAN KAFE CHILLER MENGGUNAKAN ISO 31000 - Lusya Lestari; Mutiara Putri Utami; Riko Ikhsanudin; Taofik Hidayat; Syti Sarah Maesaroh (Politeknik Bisnis Indonesia, 2022)
The large number of activities carried out in the production process at the cafe can pose a risk of work accidents. The importance of occupational safety and health (K3) which must be implemented by business actors, especially cafes, can help minimize or prevent the possibility of the risk of work accidents. This study aims to find out what could be a risk of work accidents in the production process in cafes and what actions should be taken as a form of prevention. This study uses a qualitative approach with a case study research design. Data collection was carried out by means of observation and interviews with samples of Chiller Cafes in Tasikmalaya City, besides that the data analysis technique used a risk management process based on ISO 31000 standards. The results showed that there were several possible risks that could occur in the production process at Chiller Cafes and there were several actions that can be done to minimize the possibility of these risks occurring.